TikTok Shopping Surge: Impact on Consumer Behaviour in Klang Valley, Malaysia - Munap, Rudzi Binti; Obeto, Mercy Nwadiuto; Salean, Sasileelah A. P.; Hamid, Siti Nurzana Binti Abd; Salleh, Siti Nor Asura Binti Mohamed (International Review of Management and Marketing, 2024)
TikTok shop app is an application that is currently very popular with the public. This study aims to examine the relationships on how Klang valley consumers who use TikTok shop app response towards price of products, user-friendly social media features and social media influencers. A total of 384 TikTok shop app users were included in the quantitative research. Using a 5-pt Likert scale of 1 = strongly disagree to 5 = strongly agree, price of product, user-friendly social media feature, social media influencer towards consumer purchasing behaviour were measured. The analyses of the data were carried out using SPSS and AMOS software. The measurement model confirms that the TikTok App purchasing behaviour model fits the data. The Structural equation model showed that there was a positive relationship between price of product and consumer purchasing behaviour. However, there was no significant relationship between user-friendly social media features and consumer purchasing behaviour. Furthermore, social media influencer mediates the relationship between price of product and consumer purchasing behaviour but does not mediate the relationship between user-friendly social media features and consumer purchasing behaviour. This study contributed theoretically to the emergence of the TikTok App consumer purchasing behaviour model.